grammer in CNF will be,

S-->AS/ SA/ AS'/ A'B/ a

A-->AS'/ A'B/ AS/ SA/ a/ b

S'-->SA

A'-->a

B-->b

S-->AS/ SA/ AS'/ A'B/ a

A-->AS'/ A'B/ AS/ SA/ a/ b

S'-->SA

A'-->a

B-->b

The Gateway to Computer Science Excellence

+1 vote

Convert the following context free grammar into Chomsky Normal Form:

$S \rightarrow ASA | aB$

$A \rightarrow B | S$

$B \rightarrow b | \epsilon$

**Does the appearance of starting symbol S at RHS impacts the conversion from CFG to CNF?**

0

Nitish, Typo! second line productions are for A, not for A'.

secondly A->b is missing, added due to null- productions removal.

secondly A->b is missing, added due to null- productions removal.

0

@nitish my doubt was if starting variable S appears at RHS in the original Grammar, do we need to add a temp variable? such as

S0->S

+

Original Productions

and the we start conversion from cfg to cnf?

S0->S

+

Original Productions

and the we start conversion from cfg to cnf?

52,375 questions

60,615 answers

202,053 comments

95,433 users